2010
DOI: 10.1016/j.healthplace.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related risks among street youth in two neighborhoods in a Canadian setting

Abstract: We compared drug-related behaviors, including initiation of drug use, among street youth residing in two adjacent neighborhoods in Vancouver. One neighborhood, the Downtown Eastside These results demonstrate the importance of considering neighborhood variation when developing interventions aimed at reducing drug related harms among street-involved youth at various levels of street entrenchment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
8
0
3
Order By: Relevance
“…The Downtown South neighbourhood of Vancouver is within easy walking distance of the DTES and is also the site of a thriving, albeit more “closed,” drug market (Fast, Small, Wood, & Kerr, 2009). This mixed residential-business-entertainment district is a popular destination for young people who use drugs on the streets, including opioids, cocaine, crack cocaine, and crystal methamphetamine (Bungay et al, 2006; Werb et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The Downtown South neighbourhood of Vancouver is within easy walking distance of the DTES and is also the site of a thriving, albeit more “closed,” drug market (Fast, Small, Wood, & Kerr, 2009). This mixed residential-business-entertainment district is a popular destination for young people who use drugs on the streets, including opioids, cocaine, crack cocaine, and crystal methamphetamine (Bungay et al, 2006; Werb et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these findings emphasize need for expanding youth addiction treatment and addiction treatment opportunities integrated with low-threshold housing options for homeless youth faced with addiction (Hadland et al, 2009), as well as harm reduction services, such as needle and crack pipe distribution targeted to youth engaged in high intensity drug use (Kerr et al, 2010; Ti et al, 2011; Tyndall et al, 2003). Finally, high-intensity drug use and exposure to associated harm is less well characterized among youth than among older drug users and should continue to be studied given the results of the current study and recent literature identifying the specific drug use patterns and service needs of street-involved youth (Chami et al, 2013; Hadland et al, 2009; Werb et al, 2010). …”
Section: Discussionmentioning
confidence: 97%
“…While homelessness may be indicative of entrenchment in drug scenes (Werb et al, 2010), it has been suggested that homeless youth may increasingly turn to drug use in order to cope with circumstances of life on the street. For example, homeless youth have reported the use crystal methamphetamine to stay alert, keep warm and enhance social interactions (Bungay et al, 2006), manage the psychological burdens associated with street involvement or self-medicate when contending with untreated mental disorders (Baron, 1999; Greene et al, 1997; Kirst et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Youth who are street-involved are known to engage more frequently in risky practices such as substance use, drug dealing, survival sex work, and unprotected sex. 46 As a result, street-involved youth are at risk of long-term health consequences including transmission of human immunodeficiency virus (HIV), hepatitis C virus (HCV), and other sexually transmitted infections (STIs). 7, 8 …”
Section: Introductionmentioning
confidence: 99%